A Successful CFD-Based Solution to a Water Condensation Problem in a Hard Disk Drive Factory - Jatuporn Thongsri (My University, 2017)
This paper was intended as an article of a practical solution. The settings of a ventilation system for a production line in a hard disk drive (HDD) factory were inappropriate leading to a condensation problem in a work area causing the finished products to be defective and unsalable. This paper describes an attempt to solve this problem and the outcome. Computational fluid dynamics (CFD) was used to simulate the airflow from a ventilation system in an HDD factory. The simulation results were validated with actual values measured with instruments readily available at the factory. The simulation results showed that the airflow patterns and temperature distribution of the air above and around some areas in the production line were not proper. The old temperature setting of the system for the air coming out of the inlet caused the temperature of the air above the said areas to be in the range of 13-20.5 °C, which was lower than the dew point temperature thus causing a condensation problem. From the results of the simulation, we recommended the factory to increase the inlet air temperature to be around 16.5-22 °C, so that the temperature of the air above and around the work areas would be higher than the dew point temperature and more uniform. The factory implemented our recommendation and found that it not only solved the problem satisfactorily but also saved the air-conditioning cost.
Keywords: Dew point; Factory (object-oriented programming); Dew; Aerodynamics and Fluid Dynamics Research